Factores de rigidez de membrana para la modelación de mampostería de ladrillo y bloque en edificaciones de hormigón armado - Washington Stalin, Solís Shiqui (2020)
According to the characteristics that predominate in the constructions of our environment, most of the structures are framed with a reinforced concrete and filled with masonry walls, which can be brick, block and gypsum. The presence of masonry walls in a structure before seismic solicitations generates changes in the center of masses, and if they are located in the frames, the rigidity in the first cycles of the earthquake varies. This behavior causes changes in the eccentricity of the floor, which can generate the phenomenon known as torsion in the floor and in turn causes serious structural damages and even the collapse of a structure. The analysis of the masonry walls confined in a building with the presence of lateral loads must be performed as a diagonal compression. This process is extensive and complex; or this reason, it is not customary to analyze and design specific structures for the presence of confined masonry. In this work, membrane stiffness factors were obtained for "Shell" type elements, used confined masonry to model in reinforced concrete buildings. For which, different types of structural configurations modeled with equivalent diagonals were analyzed and the results were compared with the structures modeled with "Shell" type elements, varying the membrane stiffness factors, until obtaining similar values by modeling with equivalent diagonals were obtained. In this investigation, the gypsum masonry was not taken into account, since it does not generate a significant change in the mass and rigidity of the structure.